Structural Analysis of SARS-CoV-2 ORF8 Protein: Pathogenic and Therapeutic Implications - Valcarcel, Antonio; Bensussen, Antonio; Álvarez-Buylla, Elena R.; Díaz, José (Frontiers in Genetics, 2021)
Current therapeutic strategies and vaccines against SARS-CoV-2 are mainly focused on the Spike protein despite there are other viral proteins with important roles in COVID-19 pathogenicity. For example, ORF8 restructures vesicular trafficking in the host cell, impacts intracellular immunity through the IFN-I signaling, and growth pathways through the mitogen-activated protein kinases (MAPKs). In this mini-review, we analyze the main structural similarities of ORF8 with immunological molecules such as IL‐1, contributing to the immunological deregulation observed in COVID-19. We also propose that the blockage of some effector functions of ORF8, such as the mTORC1 activation through MAPKs 40 pathway, with Rapamycin, can be a promising approach to reduce COVID-19 mortality